The potential for crop insurance reform. Issue 4 (28th October 2014) - D. Paulson, Nicholas; Babcock, Bruce; Coppess, Jonathan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to discuss the growth and rising costs association with the Federal Crop Insurance program in the USA, justifications for public support, and recent reforms that have been implemented or proposed to reduce program costs. It also analyzes a specific policy to reduce premium assistance spending. Design/methodology/approach – Data from the Risk Management Agency are used to illustrate historical trends in crop insurance program costs and to analyze the impacts of imposing a per acre cap on premium assistance. Findings – Imposing a per acre cap on premium assistance could achieve significant savings. A $20 per acre cap is estimated to reduce premium subsidy expenditures by more than 40 percent. However, the impact of such a policy would be most severe on crops currently receiving the largest subsidies per acre, which happen to be some of the largest program crops in the USA. Originality/value – This paper adds to the literature analyzing potential reform in crop insurance industry. The subsidy cap considered has been proposed and considered by policy makers, and this paper provides estimates for its potential savings.